The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep38590
|View full text |Cite
|
Sign up to set email alerts
|

From Function to Phenotype: Impaired DNA Binding and Clustering Correlates with Clinical Severity in Males with Missense Mutations in MECP2

Abstract: Mutations in the MECP2 gene cause Rett syndrome (RTT). MeCP2 binds to chromocentric DNA through its methyl CpG-binding domain (MBD) to regulate gene expression. In heterozygous females the variable phenotypic severity is modulated by non-random X-inactivation, thus making genotype-phenotype comparisons unreliable. However, genotype-phenotype correlations in males with hemizygousMECP2 mutations can provide more accurate insights in to the true biological effect of specific mutations. Here, we compared chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…No significant difference in the protein-chromocenter localization was noted, indicating that mislocalization of protein is unlikely to be involved in the etiopathogenesis of p.Ala2Val. Additionally, there were no significant differences in the average number and size of chromocenters in cells transfected with the WT and mutant MeCP2_E1 constructs, which rules out an effect of the mutation on the clustering and overall chromatin organization (33).…”
Section: Discussionmentioning
confidence: 90%
“…No significant difference in the protein-chromocenter localization was noted, indicating that mislocalization of protein is unlikely to be involved in the etiopathogenesis of p.Ala2Val. Additionally, there were no significant differences in the average number and size of chromocenters in cells transfected with the WT and mutant MeCP2_E1 constructs, which rules out an effect of the mutation on the clustering and overall chromatin organization (33).…”
Section: Discussionmentioning
confidence: 90%
“…Both the variable severity of the clinical phenotype and functional studies have shown that MECP2 mutations do not always result in the complete loss of protein function. We have recently shown that variation in the clinical severity and diminished functionality for mutations at specific MeCP2 amino acid residues is related to the physical and chemical properties of the substituting amino acid (Sheikh et al., ). Here we found that the p.Arg190His mutation (the substitution of one positively charged amino acid with histidine, which is largely uncharged at pH 7.4 but still retains some ability to bind the DNA) within the AT‐Hook1 domain does not result in the complete loss of MECP2‐DNA binding, whereas loss of DNA compaction was observed in vitro (Figure C).…”
Section: Discussionmentioning
confidence: 99%
“…These results, obtained using an AT‐rich double stranded DNA substrate, were corroborated using DNA from the BDNF ‐148 bp promoter sequence (Figure A–C), with the binding rate differing for p.Arg190, p.His190, and p.Cys190 (Figure D). Previously we reported that several residues from the distal part of MBD and ID (p.Asn126, p.Ala140, p.Pro152, p.Arg167) may contribute either to the structural integrity of the MECP2 protein, or to the binding of other nuclear proteins, which is crucial for the proper clustering of chromatin (Sheikh et al., ). Here, we propose another mechanism, that mutation within the AT‐hook1 site in MECP2 can also disrupt DNA compaction, suggesting that AT‐Hook1‐DNA binding is also crucial for chromatin clustering and correctly compacting chromatosomes to ensure proper chromosomal condensation (Figure C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations